Swine-Specific PCR-RFLP Assay Targeting Mitochondrial Cytochrome B Gene for Semiquantitative Detection of Pork in Commercial Meat Products - M. Eaqub, Ali; Uda, Hashim, Prof. Dr.; S., Mustafa; Yaakob, Che Man (Springerlink, 2011)
Link to publisher's homepage at http://www.springerlink.com